MPMC and MCMD: Free High‐Performance Simulation Software for Atomistic Systems. Issue 11 (6th August 2019) - Franz, Douglas M.; Belof, Jonathan L.; McLaughlin, Keith; Cioce, Christian R.; Tudor, Brant; Hogan, Adam; Laratelli, Luciano; Mulcair, Meagan; Mostrom, Matthew; Navas, Alejandro; Stern, Abraham C.; Forrest, Katherine A.; et al.
Abstract: Advancements in parallel computing and hardware have allowed computational exploration of chemical systems of interest with unprecendented accuracy and efficiency. The typical development of molecular simulation software is initially inspired by a particular scientific inquiry. The softwares presented herein, MPMC (Massively Parallel Monte Carlo) and MCMD (Monte Carlo/Molecular Dynamics) were born out of a pursuit to simulate condensed phase physical and chemical interactions in porous materials. MPMC first began in 2005 and has been used for dozens of published results in the literature but has not yet been introduced in a standalone paper. MCMD is a more recent expansion and re‐write with some published work, focused on adding molecular dynamics algorithms for transport and other time‐dependent properties of chemical systems. Each software functions as a standalone with some unique and other overlapping features. A driving aim of this work is to consider periodic, long‐range polarization effects in classical simulation, and both codes are optimized to perform such calculations. Sample results will be presented which highlight methodically that inclusion of explicit polarization produces simulation results with predictive power which in general are in greater agreement with experiment than non‐polarizable analogous simulations. Abstract : Massively Parallel Monte Carlo (MPMC) and Monte Carlo Molecular Dynamics (MCMD) are introduced as open‐source computer simulation software especially suited for high accuracy empirical modeling of atomistic systems with built‐in polarizable forcefields. A distinguishing feature is the application of the Thole method with refinements from Applequist and McLaughlin for polarization energy and force calculation in large, periodic systems.